A Pathogen and a Non-pathogen Spotted Fever Group Rickettsia Trigger Differential Proteome Signatures in Macrophages - Curto, Pedro; Santa, Cátia; Allen, Paige; Manadas, Bruno; Simões, Isaura; Martinez, Juan J. (Frontiers in Cellular and Infection Microbiology, 2019)
We have previously reported that Rickettsia conorii and Rickettsia montanensis have distinct intracellular fates within THP-1 macrophages, suggesting that the ability to proliferate within macrophages may be a distinguishable factor between pathogenic and non-pathogenic Spotted fever group (SFG) members. To start unraveling the molecular mechanisms underlying the capacity (or not) of SFG Rickettsia to establish their replicative niche in macrophages, we have herein used quantitative proteomics by SWATH-MS to profile the alterations resulted by the challenge of THP-1 macrophages with R. conorii and R. montanensis. We show that the pathogenic, R. conorii, and the non-pathogenic, R. montanensis, member of SFG Rickettsia trigger differential proteomic signatures in macrophage-like cells upon infection. R. conorii specifically induced the accumulation of several enzymes of the tricarboxylic acid cycle, oxidative phosphorylation, fatty acid -oxidation and glutaminolysis, as well as of several inner and outer membrane mitochondrial transporters. These results suggest a profound metabolic rewriting of macrophages by R. conorii towards a metabolic signature of an M2-like, anti-inflammatory activation program. Moreover, several subunits forming the proteasome and immunoproteasome are found in lower abundance upon infection with both rickettsial species, which may help bacteria to escape immune surveillance. R. conorii-infection specifically induced the accumulation of several host proteins implicated in protein processing and quality control in ER, suggesting that this pathogenic Rickettsia may be able to increase the ER protein folding capacity. This work reveals novel aspects of macrophage-Rickettsia interactions, expanding our knowledge of how pathogenic rickettsiae explore host cells to their advantage.